2019
DOI: 10.1097/dad.0000000000001418
|View full text |Cite
|
Sign up to set email alerts
|

Acral Lentiginous Melanomas Harbour Intratumor Heterogeneity in BRAF Exon 15, With Mutations Distinct From V600E/V600K

Abstract: The choice of appropriate therapeutic strategies may be influenced by intratumor heterogeneity and makes cancer treatment considerably more challenging. We aimed to evaluate the heterogeneity of BRAF exon 15 mutations in different areas of acral lentiginous melanoma (ALM). The entire exon 15 was sequenced in 4 different areas of paraffin-embedded samples from 26 patients with ALM. A total of 26 of 49 cases of ≥1 mm in depth of ALM identified by clinical, anatomical, and pathological data fulfilled the inclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Heterogeneity within and between tumors has been described in different tumor types and organs (Bonin & Stanta, ; Burrell, McGranahan, Bartek, & Swanton, ; Carapeto et al, ; Comodo‐Navarro et al, ; Harbst et al, ; de Souza et al, ). We have recently reported that acral melanomas are heterogeneous at the level of gene mutation ( BRAF mutation and KIT mutation) and regarding immune‐expression of several cell‐cycle proteins (Carapeto et al, ; Comodo‐Navarro et al, ; Fernandes et al, ). Using a TMA collection of well‐characterized ALM specimens, we now demonstrate that IMPDH RR structures are present increased in ALM, but there is heterogeneity in the frequency of RR‐positive cells across different sections of a given ALM specimen.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity within and between tumors has been described in different tumor types and organs (Bonin & Stanta, ; Burrell, McGranahan, Bartek, & Swanton, ; Carapeto et al, ; Comodo‐Navarro et al, ; Harbst et al, ; de Souza et al, ). We have recently reported that acral melanomas are heterogeneous at the level of gene mutation ( BRAF mutation and KIT mutation) and regarding immune‐expression of several cell‐cycle proteins (Carapeto et al, ; Comodo‐Navarro et al, ; Fernandes et al, ). Using a TMA collection of well‐characterized ALM specimens, we now demonstrate that IMPDH RR structures are present increased in ALM, but there is heterogeneity in the frequency of RR‐positive cells across different sections of a given ALM specimen.…”
Section: Discussionmentioning
confidence: 99%
“…3,22,40 KIT mutations activate both the mitogen-activated protein kinase and PI3K/AKT pathways. 41 Most KIT mutations described in acral Activated in more than 90% of melanomas 7 Stimulated by activating BRAF and NRAS mutations and inactivating NF1 mutations 5 Stimulated by upstream receptor tyrosine kinases (eg, KIT ) 8 Collateral effects allow tumor to evade immune system 5 Constitutive activation of this pathway demonstrated in ALM (in situ and invasive) and the AM group as a whole 5,9 PI3K/AKT/PTEN 5 Permits cellular survival (antiapoptotic) 10 PTEN antagonizes the PI3K/AKT/mTOR pathway, acts as a tumor suppressor 10 Stimulated by upstream receptor tyrosine kinases (eg, KIT ) 8 JAK/STAT3 5 Regulates cellular proliferation, differentiation, migration, and survival (context dependent) 11 Regulates the PD-1 immune checkpoint, a mechanism of immune escape for melanomas 12 May correlate with more advanced AM 5 TERT 5 Regulates telomere maintenance 13 TERT activation essential in tumor development Confers immortality to melanoma cells by maintaining telomere length 13 Abnormally activated in 37% of AM patients in 1 study 14 CDK4/CDKN2A 5 Directs the cell cycle CDK4 = an oncogene CDKN2A = a tumor suppressor gene that encodes p16 RB1 and p53 also involved in this pathway Also stimulated by the MAPK pathway via cyclin D1 15…”
Section: Capsule Summary Dmentioning
confidence: 99%
“…Analysis of a single clone of tumor cells may disregard important driver mutations in other tumor clones. 7 , 29 , 30 Molecular alterations leading to tumor progression and metastases are poorly understood.…”
Section: Tumor Genetics Of Acral Melanomamentioning
confidence: 99%
See 2 more Smart Citations